Pendampingan Brigade Pangan Marsada Batu Horpak di Desa Batu Horpak Tapanuli Selatan - Yusra Muharami Lestari; Ilham Arifin (LSM Catimore dan Sahabat, 2026)
The Food Brigade Program is one of the government’s strategic initiatives to strengthen national food security and rice self-sufficiency through institutional strengthening, land optimization, and the application of agricultural mechanization. This article aims to analyze the implementation and outcomes of the mentoring activities of the Marsada Batu Horpak Food Brigade in Batu Horpak Village, Tano Tombangan Angkola District, South Tapanuli Regency. The implementation method was carried out through six systematic stages: (1) identification of initial regional conditions; (2) participatory activity planning; (3) assistance in cultivation activities; (4) assistance in harvesting and post-harvest activities; (5) assistance in institutional strengthening and farm business management; and (6) periodic monitoring and evaluation, which were reinforced by conducting five extension activities.The results of the mentoring activities indicate that all stages were successfully implemented, as reflected in the completeness of the Food Brigade’s administrative records, strengthened institutional management, and an increase in the Cropping Index from IP 1 to IP 2.5. In addition, the mentoring activities contributed to improving institutional economic independence, as shown by the generation of income from leasing agricultural machinery assets amounting to IDR 30,400,000. Overall, the Marsada Batu Horpak Food Brigade plays an important role in increasing cropping intensity, rice productivity, institutional independence, and farmers’ welfare, thereby contributing to local food self-sufficiency efforts.